2014
DOI: 10.4172/2155-9899.1000210
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against C1q as a Diagnostic Measure of Lupus Nephritis: Systematic Review and Meta-analysis

Abstract: ObjectivesTo evaluate the diagnostic accuracy of C1q autoantibodies in identifying lupus nephritis (LN) in patients with systemic lupus erythematosus (SLE).Data sources and methodsCitation indexes were searched and 370 articles published from 1977 to 2013 were evaluated. The 31 selected studies included in the meta-analysis were cross-sectional in design. Among the 31 studies, 28 compared anti-C1q antibodies in 2769 SLE patients with (n=1442) and without a history of LN (n=1327). Nine studies examined anti-C1q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…(25,34) Patients cannot be diagnosed with LN based solely on anti-C1q antibodies. (35) However, when anti-C1q antibodies are associated with high levels of anti-dsDNA antibodies and low C3 and C4 levels in adults with SLE, the chances or renal involvement increase 15-fold. (36)…”
Section: Complementary Workupmentioning
confidence: 99%
“…(25,34) Patients cannot be diagnosed with LN based solely on anti-C1q antibodies. (35) However, when anti-C1q antibodies are associated with high levels of anti-dsDNA antibodies and low C3 and C4 levels in adults with SLE, the chances or renal involvement increase 15-fold. (36)…”
Section: Complementary Workupmentioning
confidence: 99%
“…Indeed, the strongest genetic factor associated with SLE is noted to be C1q (93 % in homozygous) and an increased genetic risk is also reported with the other components of the classical pathway (C1r, C1s, C4, C2 and C3) [ 37 ]. Genetic defects are rare events and more often SLE patients develop a secondary C1q deficiency due to the presence of anti-C1q Abs with a prevalence ranging from 30 to 70 % and in this case an association with proliferative LN is reported [ 38 ], as well as an association with hypocomplementemic urticarial vasculitis (HUV) with 3 cases encountered in this study [ 39 ]. In patients from our cohort with LN, anti-C1q Ab and anti-dsDNA Ab detection performances were close in predicting LN-A, for suspecting a proliferative class III/IV ± V LN-A, and during follow-up to evaluate the therapeutic response and flares in agreement with previous studies [ 38 , 40 ].…”
Section: Discussionmentioning
confidence: 93%
“…Genetic defects are rare events and more often SLE patients develop a secondary C1q deficiency due to the presence of anti-C1q Abs with a prevalence ranging from 30 to 70 % and in this case an association with proliferative LN is reported [ 38 ], as well as an association with hypocomplementemic urticarial vasculitis (HUV) with 3 cases encountered in this study [ 39 ]. In patients from our cohort with LN, anti-C1q Ab and anti-dsDNA Ab detection performances were close in predicting LN-A, for suspecting a proliferative class III/IV ± V LN-A, and during follow-up to evaluate the therapeutic response and flares in agreement with previous studies [ 38 , 40 ]. Anti-C1q Abs are expressed in arbitrary units (AU) and the assigned positive cut-off fixed by Werfen's laboratory using healthy controls as reference (20 AU/mL) ought to have good capacity to discriminate LN-A from LN-IR and non-LN patients (69–79 % specificity, respectively, and 60 % sensitivity both).…”
Section: Discussionmentioning
confidence: 93%
“…evaluated the diagnostic accuracy of anti-C1q in 2769 patients with SLE and suggested that anti-C1qAb, when used as a stand-alone biomarker, may have variable sensitivity and specificity values across studies. The authors concluded that while anti-C1qAb may have potential as a diagnostic test for monitoring and detecting LN in SLE patients, it would be better to consider them as part of a panel of autoantibodies ( 62 ). Regarding autoantibodies panel, the authors refer to the study of Isenberg et al, in which LN monitoring relies on anti-DNA antibodies ( 60 ).…”
Section: Anti-c1q In Lupus Nephritismentioning
confidence: 99%